2020
DOI: 10.21203/rs.3.rs-17641/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and Genetic Characteristics of Autosomal Recessive Polycystic Kidney Disease in Oman

Abstract: Background: There is a high prevalence of rare genetic disorders in the Middle East, and their study provides unique clinical and genetic insights. Autosomal recessive polycystic kidney disease (ARPKD) is one of the leading causes of kidney and liver-associated morbidity and mortality in Oman. We describe the clinical and genetic profile of cohort of ARPKD patients. Methods: We studied patients with a clinical diagnosis of ARPKD (n=40) and their relatives (parents (n=24) and unaffected siblings (n=10)) from 32… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The variant c.2702A>C has been previously reported in a large cohort of pediatric patients with autosomal recessive polycystic kidney disease (ARPKD), at compound heterozygous status (Melchionda et al, 2016) and more recently the same variant has been reported in literature as a compound heterozygote with other missense variants, in an adult patient with chronic kidney disease (CKD) of unknown etiology, who also presented a congenital hepatic fibrosis (Connaughton et al, 2019). The second variant c.4870C>T, found in the family, has been already previously detected in patients affected by ARPKD with other clinical manifestations such as developmental and speech delay, hepatomegaly, gallbladder stones, dilated segmental intrahepatic biliary radicles (Alfares et al, 2017); as this variant has been observed with high frequency in individuals living in the Middle East region, it is supposed to have a possible founder effect (Al Alawi et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…The variant c.2702A>C has been previously reported in a large cohort of pediatric patients with autosomal recessive polycystic kidney disease (ARPKD), at compound heterozygous status (Melchionda et al, 2016) and more recently the same variant has been reported in literature as a compound heterozygote with other missense variants, in an adult patient with chronic kidney disease (CKD) of unknown etiology, who also presented a congenital hepatic fibrosis (Connaughton et al, 2019). The second variant c.4870C>T, found in the family, has been already previously detected in patients affected by ARPKD with other clinical manifestations such as developmental and speech delay, hepatomegaly, gallbladder stones, dilated segmental intrahepatic biliary radicles (Alfares et al, 2017); as this variant has been observed with high frequency in individuals living in the Middle East region, it is supposed to have a possible founder effect (Al Alawi et al, 2020).…”
Section: Discussionmentioning
confidence: 85%